An aircraft accident reconstruction by numerical simulation method and investigations of impact force. (December 2022) - Li, Zhuoran; Wu, Hao; Xiao, Yonghao; Yu, Changhua; Lu, Yonggang; Li, Jifeng; Cheng, Wei; Jiang, Xidong
Highlights: The actual impact velocity and angle are identified on the basis of 17 cases of FE simulations. Impact loads for the airborne equipment is carried out. Impact forces against different targets are further discussed. Abstract: Numerical simulation method is wildly used and proved to be efficient in accident reconstruction, and in-depth conclusions might be derived from reliable simulation results. An aircraft accident reconstruction of MU5735 is carried out in this paper on the basis of public information from the Internet, as an example of application of numerical simulation method in accident reconstruction. Impact point, velocity and weight of the aircraft are firstly estimated by technical methods. Then 17 cases of numerical simulations are conducted with a refined full-scale finite-element model of Airbus A320, and several factors are further discussed, i. e., penetration depth, impact load and impact force. It indicates that, (1) according to the penetration depth in public report, the aircraft probably impacted almost vertically to the ground with a velocity of around 250 m/s; (2) there is a peak of thousands of times the gravity acceleration in fuselage's structural dynamic response and lasts for a long time, which might lead to the malfunction of the airborne equipment; (3) maxima of impact forces against different targets are mainly influenced by the materials of targets, and the peak of impact force against rigid ground is about 1.74 times larger than that against soil ground.